Retirement Ages by Socio-Economic Class - Séverine Arnold; Anca Jijiie (Risks, 2020)
We are interested in defining the optimal retirement age by socio-economic class, given a Defined Benefit and a Notional Defined Contribution scheme. We firstly implement a utilitarian framework. Depending on the risk aversion coefficients and individual time preference factors, the results differ significantly. Since this approach is individualistic, with no consensus in the existing literature on what values these parameters should take, it is not suitable to be used by policy makers. Therefore, we provide an alternative based on two accounts. We look for the retirement age allowing the accumulated value, at the last age with survivors, of the pensions received under each system, held in one account, to be close in value to the accumulated amount should the actuarially fair pension be paid, representing the second account. Our approach results in setting a lower retirement age for lower socio-economic classes and a higher retirement age for wealthier individuals.